Design and feed two models for microstrip antenna in two different feed methods and compare their properties - Ammar Mohammed; Mshari Ayed Asker Alshamri (Tikrit Journal of Pure Science)
In any wireless communication, the antenna plays a very important role. The need in this technology is to reduce the size of the antenna, weight, and cost with a low profile, high performance, and low return loss (RL), which is what researchers are striving for. This paper attempts to implement a rectangular microstrip patch antenna and analyze its performance for different types of feeding techniques. In this research, we designed two thin slice antennas fed in two different ways, using FR4 epoxy as an insulating substrate with a dielectric constant of 4.3. Copper was used as a conducting material for the radiating patch and the transmission line, with nearly similar geometrical dimensions. The first antenna has dimensions of (31x 26x1.6) m3 and the second antenna has dimensions of (30x27x1.6) m3. The first antenna operates with a coaxial probe feed technique and the second one operates with a microstrip line feed technique. The return loss for the first antenna we obtained is -26.0113dB with a standing wave voltage ratio of 1.1053 at a frequency of 3.59GHz, and -24.743GHz with a standing wave voltage ratio of 1.8908 at a frequency of 5.529GHz. The return loss for the second antenna is -27.468dB with a standing wave voltage ratio of 1.0884 at a frequency of 3.45GHz. The design, simulation, and inclusion of shapes and graphics for both antennas were done using the CST (Computer Simulation Tool) program